Effects of chlortetracycline and copper on tetracyclines and copper resistance genes and microbial community during swine manure anaerobic digestion. (August 2017) - Wang, Rui; Chen, Meixue; Feng, Feng; Zhang, Junya; Sui, Qianwen; Tong, Juan; Wei, Yuansong; Wei, Dongbin
Graphical abstract: Highlights: The predominant ARGs could be effectively reduced through mesophilic anaerobic digestion. Microbial community evolution was the main driver to the change of ARGs. Addition of CTC, Cu and CTC + Cu affected microbial community change and hindered removal of ARGs. Treponema might indicate the end of anaerobic digestion and compete with ARGs host bacteria. CTC + Cu seriously affected Treponema and ARGs during anaerobic digestion. Abstract: As antibiotic and heavy metals are over used in the livestock industry, animal manure is a reservoir of antibiotic resistance genes (ARGs). Anaerobic digestion has been reported to have the potential to reduce ARGs. However, few studies investigated whether reduction of ARGs would be affected by different external pressures including antibiotics and heavy metals during anaerobic digestion. The purpose of this study was thus to investigate effects of both chlortetracycline (CTC) and Cu on reduction of ARGs, heavy metal resistance genes (HMRGs) and mobile genetic elements (MGEs) during the swine manure anaerobic digestion. The results showed that the predominant ARGs ( tet O, tet W, tet X, tet L) could be effectively reduced (approximately 1.00 log copies/g TS) through mesophilic anaerobic digestion. Microbial community evolution was the main driver. It was interesting that Treponema might indicate the termination of anaerobic digestion and compete with ARGs host bacteria. Addition of CTC, Cu and CTC + Cu affected microbial community change and hindered removal of ARGs, especially, CTC + Cu seriously affected Treponema and ARGs during anaerobic digestion.